Simulasi Analisa Aliran Daya Pekerjaan Evakuasi Daya Penyulang Kintamani di PT PLN (Persero) UP3 Bali Timur dengan Software ETAP - Putu Eka Utama Putra; I Wayan Sukadana (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study aims to analyze the technical and economic impact of power evacuation work on the 20 kV distribution system at PT PLN (Persero) UP3 East Bali. The main problem studied is the high losses and poor voltage profile on the downstream side of the Kintamani feeder. The method used is load flow simulation using ETAP software with a comparative approach to conditions before and after power evacuation. The results showed that the active losses decreased from 1.017 MW to 0.626 MW (efficiency 38.45%), accompanied by an increase in the end voltage from 16.32 kV to 18.72 kV and 19.38 kV, thus meeting the SPLN 1:1995 standard. The reduction in losses resulted in energy savings of 3,425,160 kWh/year. From the economic side, a payback period (PBP) of 1.40 years was obtained, which shows that the project is financially feasible. In addition, the improvement of network performance also contributes to the reliability of the distribution system and the continuity of the distribution of electrical energy to customers. Thus, power evacuation work has been proven to be effective in improving power distribution efficiency, improving voltage quality, and providing significant economic benefits.